Fi-Wi Network for future cloud - Pathan, Al-Sakib Khan (IndianJournals, 2013)
This article explores the potential role of Fi-Wi (Fibre-Wireless) networks in supporting the future cloud computing model. As Fi-Wi could be the next wave of advancements in networking and communications infrastructure considering the current trends, the article analyses various facets of the issue from theoretical and practical perspectives. This is basically a tutorial article written for the wide range of general readers. Alongside clarifying various facets, we also analyse the pros and cons of the technology.